PsycEXTRA Dataset 2010
DOI: 10.1037/e524322011-001
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Violence in Major Daily Activities: United States, 2003-2005

Abstract: The routine activity approach, lifestyle perspective, and environmental criminology, all argue the risk of violence is not distributed evenly across time and space. This dissertation quantifies the risk of violence for different activities and types of place. Using data from the National Crime Victimization Survey and American Time Use Survey, activity-and place-specific rates of violence are calculated to determine (a) which activity or type of place is the most dangerous, (b) the relative risk of activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…The results were dramatic, but the categories were rather crude given the time use data available at the time. More recently, The American Time Use Survey made it possible to calculate national violent victimization rates with time denominators with more disaggregation (Lemieux 2010;Lemieux and Felson 2012). However, none of these publications were able to localize the impact of shifting population on crime concentration processes.…”
Section: Past Measurement Effortsmentioning
confidence: 98%
“…The results were dramatic, but the categories were rather crude given the time use data available at the time. More recently, The American Time Use Survey made it possible to calculate national violent victimization rates with time denominators with more disaggregation (Lemieux 2010;Lemieux and Felson 2012). However, none of these publications were able to localize the impact of shifting population on crime concentration processes.…”
Section: Past Measurement Effortsmentioning
confidence: 98%
“…Although the empirical evidence confirms the influence of public exposure associated with a longer and more frequent commute on the chance of being a victim of urban violence (Lemieux, ; Lemieux & Felson, ), the question is much less investigated for developing countries and still unexplored for Brazilian metropolitan regions. The main objective of this paper is to investigate the existence of a causal relationship between commute time and the probability of being a victim of urban violence for individuals living in Brazilian metropolitan regions, that is, to determine if a longer commute time implies a higher chance of becoming a victim of urban violence for the inhabitants in these urban centres.…”
Section: Introductionmentioning
confidence: 95%
“…Wang and Minor (2002), using US census information, found an inverse relation between accessibility to jobs and violent crime in the city of Cleveland, Ohio. Lemieux (2011) andLemieux andFelson (2012), using data from the National Crime Victimization Survey and American Time Survey, built timeadjusted measures of exposure to violent attacks that demonstrated that greater risk occurs during travel between activities, specifically, while commuting to work and school.…”
Section: Theoretical Background and Available Evidencementioning
confidence: 99%
See 1 more Smart Citation